LEAN MANUFACTURING IMPLEMENTATION IN INVENTORY CONTROL AS A REPAIR PROCESS - Fino Wahyudi Abdul (Jurnal Logistik Indonesia, 2018)
This control study was carried out at the PT AW Printing Company which had quite a number of problems that were often used from its store. The approach is action research with a focus on distributing and storing raw materials for lean manufacturing. The analysis is production staff who need a lot of excess paper that can still be used, and use too much paper in print production. The company then enforces a new procedure that is not possible to get printouts that can still be used using the principle of 7 waste, to use those that cannot be used. Scope of study for the process of distribution, selection and use of raw materials, understanding the meaning of supply preparation (logistics) by employees and delivery of finished products. The results of the study show that product delivery is low to customers because of the low inventory turnover. In the PT XY preparation division, there are approximately 80% of which have potential factors. The contributing factors are long demand for goods, unclear forecasting, not understood standards for demand, inaccurate recording, vital factors affecting raw materials is the selection and use of raw materials.